US Internal Security Assistance to South Vietnam: Insurgency, Subversion and Public Order, 1st Edition - Rosenau, William (Routledge, 2020)
This new study of American support to the regime of Ngo Dinh Diem in South Vietnam illuminates many contemporary events and foreign policies.